A method for preparing low-silver-content nano-scale silver-coated copper powder in a limited area
Through the limited-domain synthesis method in Schiff alkali crosslinking network micro reactor, the problem of difficulty in synthesizing nano-sized silver-clad copper powder in the prior art under mild conditions is solved, and the requirements of dense uniform coating and high performance of the silver layer are achieved.
Patent Information
- Application Number
- CN202410695214.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-05-31
AI Technical Summary
It is difficult to synthesize low-silver content nano-sized silver-clad copper powder with dense and uniform silver layer, high conductivity and oxidation resistance under mild conditions.
The Schiff alkali crosslinking network was used as a micro reactor, and the silver salt solution was slowly added to the copper powder precursor solution through the domain-limiting synthesis method. After the reaction, the decrosslinking agent was added to perform solid-liquid separation to obtain nano-sized silver-clad silver-clad copper powder.
The uniform and dense coating of the silver layer is achieved, with high conductivity and oxidation resistance, the silver source utilization rate is as high as 90-99%, the silver content can be controlled between 10%-35%, the powder resistivity is 10-30μΩ·cm, and the initial lifting temperature of the thermogravimetric weight is between 260-360℃.
Smart Images

Figure CN118477998B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing silver-coated copper powder, in particular to a method for confined preparation of nano-scale silver-coated copper powder with low silver content. Background Art
[0002] Copper and silver nanoparticles and submicron particles have been widely used in many fields due to their advantages such as low sintering temperature, good mechanical properties, high electronic conductivity and good thermal conductivity. Such as conductive inks, wiring materials, chip attach materials, electrodes in flexible integrated circuits, etc. Compared with traditional bulk soldering / interconnect / conductive materials, nano- and submicron-sized metal particles have high specific area and surface energy, so they can be sintered at a specific temperature far below the melting point of their corresponding bulk metals. After sintering, the metal particles lose their small size effect, and their melting point, electrical conductivity, thermal conductivity and mechanical properties are comparable to those of bulk metals.
[0003] However, copper particles are easily oxidized in the air due to their high metal activity, while silver particles are limited due to their poor migration resistance and high cost. The research shows that the surface silver-coated copper particles are a core-shell structure. The protection of the silver shell can enhance the antioxidant capacity of the copper particles and greatly improve the migration resistance of the silver-coated copper particles. Therefore, the synthetic silver-coated copper particles can largely retain the advantages of copper and silver particles and overcome their disadvantages.
[0004] On the basis of improving disadvantages with comprehensive advantages, reducing costs is particularly important. The current nano-level silver-coated copper powder process on the market is not mature and the process is complicated. In order to ensure the performance of silver, the silver content of the nano-level silver-coated copper powder needs to be as high as 30-40%, and the utilization rate of the silver source in the synthesis process is low. For example, in order to solve the shortcomings of the prepared micron-level silver-coated copper powder with holes on the surface and insufficient antioxidant performance, patent CN202310206946.2 needs to add a large amount of nano-silver powder to assist in optimizing performance, thus losing the meaning of reducing costs. Another example is patent CN201610219351.0, which requires heat treatment for several hours under a protective atmosphere. The conditions are harsh and the smaller the particle size, the worse the dispersibility. The powder agglomeration phenomenon is obvious, which affects subsequent applications.
[0005] In summary, compared with the existing technology, how to synthesize low-silver-content nano-scale silver-coated copper powder with dense and uniform silver layer, high conductivity and oxidation resistance under mild conditions is a difficult problem that urgently needs to be solved in this field. Summary of the invention
[0006] Purpose of the invention: The purpose of the present invention is to provide a method for confining and synthesizing a low-silver-content nanoscale silver-coated copper powder with a uniform and dense silver layer, high conductivity and oxidation resistance, using a Schiff base cross-linked network as a microreactor.
[0007] Technical solution: The method for preparing low-silver-content nano-scale silver-coated copper powder by confinement of the present invention comprises the following steps:
[0008] (1) Surface pretreatment of copper powder;
[0009] (2) mixing the pretreated copper powder with a Schiff base solution and an amino acid complexing agent to obtain a copper powder precursor solution;
[0010] (3) slowly adding the silver salt solution dropwise to the copper powder precursor solution to react; after the reaction, adding a cross-linking agent to perform solid-liquid separation, and washing and drying the obtained solid product to obtain a low-silver content nano-scale silver-coated copper powder.
[0011] Wherein, in step (2), the amine ligand forming the Schiff base is at least one of polyallylamine, polyethyleneimine, and polyetheramine; the aldehyde ligand forming the Schiff base is at least one of malondialdehyde, succinaldehyde, glutaraldehyde, dialdehyde starch, and dialdehyde polyethylene glycol; wherein the weight average molecular weight of polyallylamine is 1000-8000, the weight average molecular weight of polyethyleneimine is 600-1800, the weight average molecular weight of polyetheramine is 230-1000; and the weight average molecular weight of dialdehyde polyethylene glycol is 600-2000.
[0012] Wherein, in step (2), the solvent in the Schiff base solution is preferably water; the preparation process of the Schiff base solution is: mixing the solution of the amino ligand and the solution of the aldehyde ligand to form a Schiff base solution; the concentration of the Schiff base solution is 0.5-2.5g / L; the molar ratio of the amino group to the aldehyde group is 1:1-1:5; wherein the solvent used in the solution of the amino ligand and the solution of the aldehyde ligand is water; the mass ratio of the amino ligand to water is 1:2000-1:1000, and the mass ratio of the aldehyde ligand to water is 1:1-1:3.
[0013] Wherein, in step (2), the mass ratio of the pretreated copper powder to the Schiff base is 10:3-20:1.
[0014] Wherein, in step (2), the concentration of the copper powder precursor solution is 0.1-2 mol / L, and the particle size of the copper powder is 100-1000 nm.
[0015] Wherein, in step (2), the amino acid complexing agent is at least one of histidine, alanine, leucine, glycine, serine, valine and proline; and the molar ratio of the amino acid complexing agent to the silver salt is 1:1-5:1.
[0016] Wherein, in step (3), the molar ratio of the silver salt to the copper powder is 1:5-1:20; the silver salt solution is added at a rate of 1-10 mL / min; the reaction temperature is 30-60° C.; and step (3) is carried out under mechanical stirring at 300-600 r / min.
[0017] Wherein, in step (3), the concentration of the silver salt is 0.05-0.5 mol / L; the silver salt is preferably silver nitrate.
[0018] Wherein, in step (4), the cross-linking agent is disodium ethylenediaminetetraacetate, and its aqueous solution is acidic and can decross-link the Schiff base cross-linked network, and the molar ratio of the cross-linking agent to the imine bond in the Schiff base is 1:1-5:1.
[0019] Wherein, in step (4), the reaction liquid is filtered to separate the solid and liquid; and washed with water and ethanol respectively; then the washed silver-coated copper powder is placed in a vacuum drying oven for drying; the drying temperature is 50°C and the drying time is 6-12h; the obtained silver-coated copper powder has a particle size of 100-1000nm.
[0020] Beneficial effects: Compared with the prior art, the present invention achieves the following significant effects: (1) The present invention adds a Schiff base cross-linked network as a microreactor to realize the confined synthesis of silver-coated copper. This cross-linked network can realize pH response, so the post-treatment is simple and efficient; (2) The present invention adopts a one-step method to prepare silver-coated copper powder, the process route is simple, the conditions are mild, the cost is controllable, and it is easy to mass produce; (3) The silver-coated copper powder provided by the present invention has high sphericity, good dispersibility, and the silver layer is densely and evenly coated, and has good electrical conductivity and antioxidant properties. (4) The preparation method adopted by the present invention has a silver source utilization rate of up to 90-99%, the silver content can be controlled between 10%-35%, the powder resistivity is 10-30μΩ·cm, and the initial thermogravimetric lifting temperature is between 260-360°C, which can achieve low silver content, dense coating and high performance requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a SEM image of the silver-coated copper powder in Example 1;
[0022] Figure 2 is the SEM image of the silver-coated copper powder in Comparative Example 1;
[0023] Figure 3 is the SEM image of the silver-coated copper powder in Comparative Example 2;
[0024] Figure 4 is the SEM image of the silver-coated copper powder in Comparative Example 3;
[0025] Figure 5 is the SEM image of the silver-coated copper powder in Comparative Example 4;
[0026] Figure 6 is a SEM image of the silver-coated copper powder in Example 2;
[0027] Figure 7This is the thermogravimetric curve of the silver-coated copper powder in Example 1. DETAILED DESCRIPTION
[0028] The present invention is described in further detail below.
[0029] Example 1
[0030] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0031] (1) Pretreatment of copper powder: 5 g of copper powder was placed in 50 mL of acetone solution and subjected to ultrasonic treatment for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, subjected to ultrasonic treatment for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, subjected to ultrasonic treatment for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0032] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 1000 was dissolved in 500 ml of deionized water, and 1.2 ml of 50% glutaraldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution. The pretreated 1 μm copper powder was dispersed in the Schiff base solution, 4 g of histidine was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating at 40°C in a water bath to obtain a copper powder precursor solution.
[0033] (3) 0.85 g of silver nitrate was dissolved in 50 mL of deionized water to obtain a 0.1 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 2 ml / min for 1 h;
[0034] (4) Prepare 100 mL of 0.2 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0035] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0036] Example 2
[0037] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0038] (1) Pretreatment of copper powder: 5 g of 500 nm copper powder was placed in 50 mL of acetone solution and ultrasonicated for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, ultrasonicated for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, ultrasonicated for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0039] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 1000 was dissolved in 500 ml of deionized water, and 1.2 ml of 50% glutaraldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution. The pretreated 500 nm copper powder was dispersed in the Schiff base solution, 2.4 g of histidine was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.1 mol / L, and mechanical stirring was performed for 10 min under heating at 40°C in a water bath to obtain a copper powder precursor solution;
[0040] (3) 1.6 g of silver nitrate was dissolved in 100 mL of deionized water to obtain a 0.09 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 5 ml / min and reacted for 1 h;
[0041] (4) Prepare 100 mL of 0.1 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0042] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0043] Example 3
[0044] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0045] (1) Pretreatment of copper powder: 5 g of copper powder was placed in 50 mL of acetone solution and subjected to ultrasonic treatment for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, subjected to ultrasonic treatment for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, subjected to ultrasonic treatment for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0046] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 600 was dissolved in 500 ml of deionized water, and 1.2 ml of 50% succinaldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution. The pretreated 1 μm copper powder was dispersed in the Schiff base solution, 0.8 g of histidine was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating at 40°C in a water bath to obtain a copper powder precursor solution.
[0047] (3) 0.85 g of silver nitrate was dissolved in 50 mL of deionized water to obtain a 0.1 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 1 ml / min for 1 h;
[0048] (4) Prepare 100 mL of 0.2 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0049] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 12 h.
[0050] Example 4
[0051] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0052] (1) Pretreatment of copper powder: 10 g of copper powder was placed in 50 mL of acetone solution, and ultrasonicated for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, and ultrasonicated for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, and ultrasonicated for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0053] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 600 was dissolved in 500 ml of deionized water, and 1.2 ml of a 50% aqueous solution of dialdehyde polyethylene glycol with a weight average molecular weight of 800 was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution, and the pretreated 1 μm copper powder was dispersed in the Schiff base solution, 4 g of histidine was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating at 40°C in a water bath to obtain a copper powder precursor solution;
[0054] (3) 0.8 g of silver nitrate was dissolved in 80 mL of deionized water to obtain a 0.05 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 7 ml / min for 1 h;
[0055] (4) Prepare 100 mL of 0.2 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0056] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 12 h.
[0057] Example 5
[0058] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0059] (1) Pretreatment of copper powder: 5 g of copper powder was placed in 50 mL of acetone solution and subjected to ultrasonic treatment for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, subjected to ultrasonic treatment for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, subjected to ultrasonic treatment for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0060] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 1800 was dissolved in 500 ml of deionized water, and 1.2 ml of 50% glutaraldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution. The pretreated 1 μm copper powder was dispersed in the Schiff base solution, 1.5 g of serine was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating in a 40°C water bath to obtain a copper powder precursor solution;
[0061] (3) 0.8 g of silver nitrate was dissolved in 100 mL of deionized water to obtain a 0.04 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 10 ml / min for 1 h;
[0062] (4) Prepare 100 mL of 0.2 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0063] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 12 h.
[0064] Example 6
[0065] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0066] (1) Pretreatment of copper powder: 5 g of copper powder was placed in 50 mL of acetone solution and subjected to ultrasonic treatment for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, subjected to ultrasonic treatment for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, subjected to ultrasonic treatment for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0067] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 1800 was dissolved in 1000 ml of deionized water, and 1.2 ml of 50% glutaraldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution. The pretreated 1 μm copper powder was dispersed in the Schiff base solution, 1 g of glycine was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating in a 40°C water bath to obtain a copper powder precursor solution.
[0068] (3) 0.8 g of silver nitrate was dissolved in 50 mL of deionized water to obtain a 0.08 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 2 ml / min for 1 h;
[0069] (4) Prepare 100 mL of 0.2 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0070] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0071] Example 7
[0072] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0073] (1) Pretreatment of copper powder: 5 g of 500 nm copper powder was placed in 50 mL of acetone solution and ultrasonicated for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, ultrasonicated for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, ultrasonicated for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0074] (2) Preparation of copper powder precursor: First, 0.7 g of polyallylamine with a weight average molecular weight of 1000 was dissolved in 500 ml of deionized water, 1.5 ml of 50% dialdehyde starch aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution, the pretreated 500 nm copper powder was dispersed in the Schiff base solution, 3.7 g of proline was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating at 40°C in a water bath to obtain a copper powder precursor solution;
[0075] (3) 1.6 g of silver nitrate was dissolved in 80 mL of deionized water to obtain a 0.1 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 1.5 ml / min and reacted for 1 h;
[0076] (4) Prepare 100 mL of 0.2 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0077] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0078] Comparative Example 1
[0079] (1) 5 g of copper powder was placed in 50 mL of acetone solution, and ultrasonicated for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, and ultrasonicated for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, and ultrasonicated for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0080] (2) Dispersing the pretreated copper powder into deionized water, dissolving 4 g of histidine in 100 mL of deionized water, and mixing the two solutions. The concentration of the copper powder precursor solution is 0.2 mol / L, and the solution is heated in a water bath at 40° C. and mechanically stirred for 10 min to obtain a copper powder precursor solution.
[0081] (3) 0.85 g of silver nitrate was dissolved in 50 mL of deionized water to obtain a 0.1 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 2 ml / min for 1 h;
[0082] (4) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0083] Comparative Example 2
[0084] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0085] (1) Pretreatment of copper powder: 5 g of copper powder was placed in 50 mL of acetone solution and subjected to ultrasonic treatment for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, subjected to ultrasonic treatment for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, subjected to ultrasonic treatment for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0086] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 1000 was dissolved in 500 ml of deionized water, and 1.2 ml of 50% glutaraldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution. The pretreated 1 μm copper powder was dispersed in the Schiff base solution. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating at 40°C in a water bath to obtain a copper powder precursor solution;
[0087] (3) 0.85 g of silver nitrate was dissolved in 50 mL of deionized water to obtain a 0.1 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 2 ml / min for 1 h;
[0088] (4) Prepare 100 mL of 0.2 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0089] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0090] Comparative Example 3
[0091] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0092] (1) Pretreatment of copper powder: 5 g of copper powder was placed in 50 mL of acetone solution and subjected to ultrasonic treatment for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, subjected to ultrasonic treatment for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, subjected to ultrasonic treatment for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0093] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 1000 was dissolved in 500 ml of deionized water, and 1.2 ml of 50% glutaraldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution. The pretreated 1 μm copper powder was dispersed in the Schiff base solution, 2 g of histidine was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating at 40°C in a water bath to obtain a copper powder precursor solution;
[0094] (3) 0.85 g of silver nitrate was dissolved in 50 mL of deionized water to obtain a 0.1 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 2 ml / min for 1 h;
[0095] (4) Prepare 100 mL of 0.2 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0096] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0097] Comparative Example 4
[0098] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0099] (1) Pretreatment of copper powder: 5 g of copper powder was placed in 50 mL of acetone solution and subjected to ultrasonic treatment for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, subjected to ultrasonic treatment for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, subjected to ultrasonic treatment for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0100] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 1000 was dissolved in 500 ml of deionized water, and 1.2 ml of 50% glutaraldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution. The pretreated 1 μm copper powder was dispersed in the Schiff base solution, 4 g of histidine was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating at 40°C in a water bath to obtain a copper powder precursor solution.
[0101] (3) 0.85 g of silver nitrate was dissolved in 50 mL of deionized water to obtain a 0.1 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 2 ml / min for 1 h;
[0102] (4) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0103] Comparative Example 5
[0104] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0105] (1) Pretreatment of copper powder: 5 g of copper powder was placed in 50 mL of acetone solution and subjected to ultrasonic treatment for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, subjected to ultrasonic treatment for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, subjected to ultrasonic treatment for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0106] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 1000 was dissolved in 500 ml of deionized water, and 1.2 ml of 50% glutaraldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution. The pretreated 1 μm copper powder was dispersed in the Schiff base solution, 3 g of sodium tartrate was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating in a 40°C water bath to obtain a copper powder precursor solution.
[0107] (3) 0.85 g of silver nitrate was dissolved in 50 mL of deionized water to obtain a 0.1 mol / L silver nitrate solution, and dilute ammonia water was added dropwise under stirring until the solution became transparent, and then the solution was added dropwise into the copper powder precursor solution at a rate of 2 ml / min for reaction for 1 h;
[0108] (4) Prepare 100 mL of 0.2 mol / L disodium ethylenediaminetetraacetic acid solution, drop it into the reaction system, and allow the cross-linking reaction to proceed for 30 min;
[0109] (5) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0110] Compared with Example 1, the presence of silver tartrate in Comparative Example 5 makes the complexing mechanism of the reaction system complicated, and flocculent precipitation is produced, indicating that a stronger complexing agent needs to be selected to complex silver ions in the experiment.
[0111] Comparative Example 6
[0112] A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, comprising the following steps:
[0113] (1) Pretreatment of copper powder: 5 g of copper powder was placed in 50 mL of acetone solution and subjected to ultrasonic treatment for 20 min; filtered, and then the filter cake was placed in 50 mL of a mixed solution of 0.5 mol / L ammonium sulfate and 1 mol / L ammonia water, subjected to ultrasonic treatment for 20 min, filtered, and then the filter cake was dispersed in 50 mL of 1% sodium hydroxide solution, subjected to ultrasonic treatment for 20 min, and filtered; organic impurities and oxides on the surface of the copper powder were removed, and then the copper powder was washed with deionized water and ethanol for 3 times;
[0114] (2) Preparation of copper powder precursor: First, 0.5 g of polyethyleneimine with a weight average molecular weight of 600 was dissolved in 500 ml of deionized water, and 1.2 ml of 50% glutaraldehyde aqueous solution was added dropwise and stirred for 30 min to form a stable Schiff base cross-linked network solution, and the pretreated 1 μm copper powder was dispersed in the Schiff base solution, 6 g of disodium ethylenediaminetetraacetate was dissolved in 100 mL of deionized water, and the two solutions were mixed. The concentration of the copper powder precursor solution was 0.2 mol / L, and mechanical stirring was performed for 10 min under heating in a 40°C water bath to obtain a copper powder precursor solution;
[0115] (3) 0.85 g of silver nitrate was dissolved in 50 mL of deionized water to obtain a 0.1 mol / L silver nitrate solution, which was then dripped into the copper powder precursor solution at a drip rate of 2 ml / min for 1 h;
[0116] (4) The reaction solution was filtered to separate the solid and the liquid; the solid was washed three times with deionized water and ethanol respectively; and the washed silver-coated copper powder was placed in a vacuum drying oven at 50° C. and dried for 6 h.
[0117] Compared with Example 1, in Comparative Example 6, disodium ethylenediaminetetraacetic acid (EDTA) is added as a cross-linking agent in step (2). At this time, the cross-linking effect of disodium ethylenediaminetetraacetic acid on the Schiff base renders the cross-linked network ineffective and loses its confinement effect, indicating that when selecting a complexing agent, care must be taken not to affect the cross-linked network.
[0118] like Figure 1-6 As shown, the silver-coated copper powders of the above-mentioned Example 1, Example 2, and Comparative Examples 1-4 were tested by scanning electron microscopy; Figure 1 , 2As shown, by comparing the embodiment with comparative example 1, it can be clearly observed that in comparative example 1, there are too many black shadow holes caused by L-histidine corrosion on the copper surface, and the silver layer is not closely attached to the surface of the copper ball. It also reflects that the Schiff base also plays a certain protective role on the copper powder. Figure 7 The thermogravimetric curve shows that the powder starts to gain weight at 300°C, indicating that the silver-coated copper powder prepared in Example 1 has high antioxidant properties. The silver content in Example 1 is measured to be 11.4%, and uniform coating is achieved at a low silver content.
[0119] like Figure 1 , 3 As shown, by comparing Example 1 with Comparative Example 2, it can be observed that the silver-coated copper powder in Comparative Example 2 has more flaky silver growth, and there is almost no silver layer coating on the surface of the copper ball, indicating that the complexing effect of Schiff base on silver ions is too strong, which hinders the occurrence of replacement reaction between silver ions and the surface of the copper ball in the grid.
[0120] like Figure 1 , 4 As shown, by comparing Example 1 with Comparative Example 3, it can be observed that the silver-coated copper powder in Comparative Example 3 still has corrosion, and the utilization rate of silver is not high, which shows that the amount of amino acid chelating agent needs to be properly controlled. Too little amino acid chelating agent will cause part of the silver ions to be chelated by the Schiff base cross-linked network, and the surface of the copper ball cannot be coated with silver in time, resulting in the copper ball surface being in contact with the alkaline solution for too long and being corroded.
[0121] like Figure 1 , 5 As shown, by comparing Example 1 with Comparative Example 4, it can be observed that more copper balls in Comparative Example 4 have pit-type corrosion on their surfaces, while in Example 1, the degree of corrosion is much less than that in Comparative Example 4, indicating that the increase in the concentration of the Schiff base cross-linked network has corrosion on the copper ball surface; and after the concentration of the Schiff base cross-linked network in this comparative example increases, the dripping rate of 2ml / min is relatively slow. Too slow a dripping rate will cause the copper ball surface to be in contact with the Schiff base and L-histidine for too long, which will also cause serious corrosion of the copper ball; therefore, the increase in the concentration of the Schiff base cross-linked network and the slow addition of silver nitrate will both cause serious corrosion of the copper ball. The addition of a cross-linking agent in the late stage of the reaction helps to reduce the degree of corrosion of the Schiff base on the powder; indicating that the amount of the amino acid complexing agent needs to be properly controlled, and the cross-linking agent has a promoting effect on the reaction, otherwise the pH value of the reaction system is too high, which will cause copper to be corroded and the silver ion replacement is incomplete.
Claims
1. A method for preparing low-silver-content nano-scale silver-coated copper powder by confinement, characterized in that: The following steps are involved: (1) Pre-treating the surface of copper powder; (2) mixing the pretreated copper powder with a Schiff base solution and an amino acid complexing agent to obtain a copper powder precursor solution; The mass ratio of the pretreated copper powder to the Schiff base is 10:3-20:1; the molar ratio of the amino acid complexing agent to the silver salt is 1:1-5:1; The preparation process of the Schiff base solution is as follows: mixing the solution of the amine ligand and the solution of the aldehyde ligand to form a Schiff base solution; the concentration of the Schiff base solution is 0.5-2.5g / L; the molar ratio of the amine group to the aldehyde group is 1:1-1:5; (3) slowly adding the silver salt solution dropwise to the copper powder precursor solution to react; after the reaction, adding a cross-linking agent to perform solid-liquid separation, and washing and drying the obtained solid product to obtain a low-silver content nano-scale silver-coated copper powder; The molar ratio of the silver salt to the copper powder is 1:5-1:20; the silver salt solution dropping speed is 1-10mL / min; the reaction temperature is 30-60°C; and the silver salt concentration is 0.05-0.5mol / L.
2. The method for preparing low-silver-content nano-scale silver-coated copper powder by confinement according to claim 1, characterized in that: In step (2), the amine ligand forming the Schiff base is at least one of polyallylamine, polyethyleneimine, and polyetheramine; the aldehyde ligand forming the Schiff base is at least one of malondialdehyde, succinaldehyde, glutaraldehyde, dialdehyde starch, and dialdehyde polyethylene glycol.
3. The method for preparing low-silver-content nano-scale silver-coated copper powder by confinement according to claim 1, characterized in that: In step (2), the concentration of the copper powder precursor solution is 0.1-2 mol / L, and the particle size of the copper powder is 100-1000 nm.
4. The method for preparing low-silver-content nano-scale silver-coated copper powder by confinement according to claim 1, characterized in that: In step (2), the amino acid complexing agent is at least one of histidine, alanine, leucine, glycine, serine, valine, and proline.
5. The method for preparing low-silver-content nano-scale silver-coated copper powder by confinement according to claim 1, characterized in that: In step (3), the cross-linking agent is disodium ethylenediaminetetraacetate, and its aqueous solution is acidic and can decross-link the Schiff base cross-linked network. The molar ratio of the cross-linking agent to the imine bond in the Schiff base is 1:1-5:
1.
6. The method for preparing low-silver-content nano-scale silver-coated copper powder by confinement according to claim 1, characterized in that: The obtained silver-coated copper powder has a particle size of 100-1000 nm.
Citation Information
Patent Citations
Nano silver-coated copper powder and preparation method and application thereof
CN105855538A
Silver-coated copper powder and preparation method and application thereof
CN116060610A
Preparing method for non-precious metal ion complexation Schiff base graphene catalyst
CN104993160A
Nanometer material with core-shell structure using heteroatom-doped polymer as shell and preparation method thereof
CN109046191A
Cited By
Silver-coated copper powder suitable for high-frequency electronic component and preparation method of silver-coated copper powder
CN122142319A